Effect of rotary plow with different blades, plow cover height and different forward speed on some soil physical traits - Ahmed Kadhim Abbood; Majed Salih Himoud (University of Thi-Qar Journal of agricultural research, 2023)
This research was conducted to study the effect of different forms of rotary plow blades s on clay loam soils, through the use of three forms of blades (traditional blades (T1) and locally manufactured blades (T2 and T3)), and two forward plowing speeds (3.85 and 6.04) km. ̄ ¹ hour, two rotary tiller hood opening angles (35˚ and 70˚)and the study of its effect on the physical properties of clay soil: penetration resistance, average volume of stirred soil, percentage of earth masses with diameters less than 5 cm m², bulk density of soil, and total porosity. The research was carried out using the split split plank method according to the randomized complete block design (C.R.D) and with three replicates for each treatment. The results showed that the forward speed (3.85) kmh ̄ ¹ has achieved the best soil resistance to penetration. While the forward velocity (6.04) kmh ̄ ¹ achieved the best values for each soil volume rate, soil bulk density and total porosity. The angle (35˚) recorded the best values for each of the soil resistance to penetration and the proportion of soil masses, while the angle (70˚) excelled in recording the best values for each average of the volume of the soil stirred up, bulk density and porosity. The blades ((T3) was significantly excelled on the two blades (T1 and T2) in achieving the best values of penetration resistance, average volume of soil stirred up, mass ratio, bulk density, and porosity. As for the overlap between the two forward speeds and cover angles of the plow, the speed was (3.85) km per hour ̄ ¹ With angle ((35˚) best values for penetration resistance,As for the speed (6.04) km h ̄ ¹ with an angle ((70˚), the best values were recorded for the average volume of the stirred soil, bulk density and porosity. As for the interaction between the two speeds and the shape of the blades, the blades (T3) excelled at the forward speed (3.85) km/h ̄ ¹ in giving the best value for resistance to penetration. While the blades itself gave at the speed (6.04) kmh ̄ ¹ the best values for the average volume of soil stirred up. As for the overlap between the angles of cover for the plow and the shape of the blades, the blades (T3) excelled at the angle (70˚) in achieving the best values for the average volume of soil stirred up and density virtual and porous, At the angle (35˚), the blades achieved the best value of penetration resistance and the percentage of soil masses. As for the interaction between the two forward speeds of plowing, the angles of the opening of the rotary plow cover and the shape of blades, there were no significant differences in the physical traits of soil.